Chapter 4: Seed Quality and Seeding Technology - Kent Cushman (EDIS, 2019)
Quality seed is defined as varietally pure with a high germination percentage, free from disease and disease organisms, with a proper moisture content and weight. Quality seed insures good germination, rapid emergence, and vigorous growth. These aspects translate to a good stand (whether greenhouse or field). Poor quality seed results in "skips," excessive thinning, or yield reductions due to overcrowding, all of which diminish profitability. This document is HS713, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.